Low computations in compression image schemes using Cache codebook based on Weber’s law - Hameed , Maha Ahmed (Iraqi Journal of Science, 2022)
In this paper, we have employed a computation of three technique to reduce the computational complexity and bit rate for compressed image. These techniques are bit plane coding based on two absolute values, vector quantization VQ technique using Cache codebook and Weber’s low condition. The experimental results show that the proposed techniques achieve reduce the storage size of bit plane and low computational complexity.